Analysis And Planning of Bored Pile Foundation In Double Train Bridge Way Changes In Central Lampung Regency - Hendri, Adit Pratama; Arifaini, Nur; Adha, Idharmahadi (Universitas Lampung, 2019)
Indonesia has considerable coal reserves, but only a few or even very few can be exploited. The potential of coal owned by South Sumatra Province is known to reach around 85% of the total reserves contained in Sumatra, or around 22.24 billion tons. This means that even though mining is maximized to 50 million tons per year, coal will not be mined for 200 years. To maximize the potential of available coal, modes are needed from the train, but for now there is only one mode used to extract coal from it to transport coal from Tarahan - Tanjung Enim or vice versa. So to maximize the coal's potential, the Ministry of Transportation through the Directorate General of Railways plans to build a double track railway line between Tarahan - Tanjung Enim, one of the roads going through the river is needed a bridge to facilitate the train journey to transport the coal. The railroad bridge that was built was located in KM132 in the burial way of Central Lampung Province. In this bridge construction, the carrying capacity of the foundation needs to be analyzed so that it can withstand the burden of the upper structure and the train.From the results of the study showed that the analysis of the carrying capacity of the permit pile of 1700 kN was greater than the maximum carrying capacity that burdened the pile of 1508.93 kN so that it could be concluded that the structure under the bridge was able to withstand the load from the upper structure. Keywords: analysis, coal, bridge, carrying capacity.